2022
DOI: 10.1136/gutjnl-2021-326828
|View full text |Cite
|
Sign up to set email alerts
|

Postinfective bowel dysfunction followingCampylobacter enteritisis characterised by reduced microbiota diversity and impaired microbiota recovery

Abstract: ObjectivesPersistent bowel dysfunction following gastroenteritis (postinfectious (PI)-BD) is well recognised, but the associated changes in microbiota remain unclear. Our aim was to define these changes after gastroenteritis caused by a single organism, Campylobacter jejuni, examining the dynamic changes in the microbiota and the impact of antibiotics.DesignA single-centre cohort study of 155 patients infected with Campylobacter jejuni. Features of the initial illness as well as current bowel symptoms and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…After removing duplicates and records published before 2018, 765 records were screened for titles and abstracts. Of these, 23 reports were assessed for their eligibility, and 11 complied with the inclusion criteria [23][24][25][26][27][28][29][30][31][32][33].…”
Section: Search Resultsmentioning
confidence: 99%
“…After removing duplicates and records published before 2018, 765 records were screened for titles and abstracts. Of these, 23 reports were assessed for their eligibility, and 11 complied with the inclusion criteria [23][24][25][26][27][28][29][30][31][32][33].…”
Section: Search Resultsmentioning
confidence: 99%
“…When it comes to perturbations such as infections and changes in the diet, a healthy gut microbiome is resilient to disturbance and able to recover the original composition whereas a non-resilient microbiome may shift to a maladaptive status of dysbiosis. 22 The previous study showed that the Coxsackievirus -infected mouse gut virome changed vastly and had significant alterations in the alpha diversity and beta diversity during the progression of virus infection. 23 Lu et al identified a significantly lower alpha diversity of the gut virome in diarrheal dairy calves.…”
Section: Discussionmentioning
confidence: 99%
“…3e). Campylobacter is a landmark genus causing enteritis [97], indicating increased disease risks. Conversely, the Odoribacter has been shown to able to effectively limit intestinal inflammation [98], this indicates that the microbiota in the jejunal digestion site of goats has the potential role of resisting intestinal inflammation.…”
Section: Microbial Community Dynamics Along Goat Git Were Driven By D...mentioning
confidence: 99%